Mac OS X 10.4 Tiger - Williams, Robin 1953- (Peachpit, 2005)
If you want to tame Mac OS X Tiger, but you want to do so in the comfort of your own home, this guide makes it possible! Robin Williams uses her trademark friendly teaching style to reveal exactly what you want to know: What's new in Tiger, what's great about it, and how can you get the most out of it fast! Focused lessons take you step-by-step through practical, real-world projects that teach Mac OS X Tiger inside and out. Covers everything from upgrading your Mac to Tiger and customizing and troubleshooting your system to all of Tiger's new goodies: configuring the spoken-user interface, audio and video messaging with multiple people at once, a Dashboard full of Widgets, the innovative Spotlight Search system, the enhanced Safari RSS browser, and more.
Includes index. - Print version record
Keywords: Mac OS; Electronic data processing personnel -- Study guides -- Certification; Electronic data processing personnel; Certification; Study guides; Electronic data processing personnel; Certification; examination study guides; Study guides; Guides de l'étudiant